Attitudes Towards Justice and Social Reconstruction in Bosnia and Herzegovina and Croatia - Biro, Mikloš (Array, 2004)
In this study we examined the factors that may contribute to or prevent the rebuilding of war-torn societies, based on two surveys of attitudes and beliefs of the inhabitants of three cities – Vukovar, Mostar and Prijedor – in 2000 and 2002. The main goals of our study were: to investigate some of the underlying attitudes and beliefs of the population of Mostar, Prijedor and Vukovar toward the rebuilding of community and reconciliation. The total sample of the survey consisted of 1624 participants, divided equally among national groups in each city. The questionnaire consisted of 68 items and contained three scales and questions about attitudes toward nationalism and xenophobia, other national groups, reconciliation, the ICTY and war crimes, as well as questions about prior experience with members of the other national groups, traumatic experiences during the war and demographic data. The results suggest that authoritarianism, nationalism and ethnocentrism may be the most important obstacles to the process of reconciliation among ethnic groups in target communities. An important finding is that the level of traumatic experience by itself is not a significant predictor of reconciliation. However, when combined with negative experience with opposing group trauma becomes a serious obstacle. The relationship between trauma and the attitudes towards ICTY trials is even less clear, and the role of the ICTY in promoting reconciliation is far from being perceived as accomplished.